2022
DOI: 10.1002/hon.3002
|View full text |Cite
|
Sign up to set email alerts
|

Host‐related factors and cancer: Malnutrition and non‐Hodgkin lymphoma

Abstract: Assessment of host‐related factors is a crucial aspect in the comprehensive management of cancer patients. A distinct nutritional disturbance linked to cancer has been recognized to be associated with negative outcomes. However, compared to solid tumors, only a limited number of studies have looked specifically at nutritional issues in the field of lymphoma. The aim of this review is to integrate the current knowledge on interactions between malnutrition and lymphoma and address most relevant and pertinent que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…In cancer patients, malnutrition is a common comorbidity and is strongly correlated with both treatment efficacy and patient survival. 12 , 13 As an efficient index for the early detection and ongoing screening of malnutrition, the controlling nutritional status (CONUT) score, originally reported in 2005, consists of total lymphocyte counts (TL), total cholesterol level (T‐CHOL), and serum albumin (ALB). 14 Currently, several studies have shown that the CONUT score has prognostic value for hematological malignancies, such as diffuse large B‐cell lymphoma (DLBCL), peripheral T‐cell lymphoma (PTCL), and multiple myeloma (MM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer patients, malnutrition is a common comorbidity and is strongly correlated with both treatment efficacy and patient survival. 12 , 13 As an efficient index for the early detection and ongoing screening of malnutrition, the controlling nutritional status (CONUT) score, originally reported in 2005, consists of total lymphocyte counts (TL), total cholesterol level (T‐CHOL), and serum albumin (ALB). 14 Currently, several studies have shown that the CONUT score has prognostic value for hematological malignancies, such as diffuse large B‐cell lymphoma (DLBCL), peripheral T‐cell lymphoma (PTCL), and multiple myeloma (MM).…”
Section: Introductionmentioning
confidence: 99%
“…In cancer patients, malnutrition is a common comorbidity and is strongly correlated with both treatment efficacy and patient survival 12,13 . As an efficient index for the early detection and ongoing screening of malnutrition, the controlling nutritional status (CONUT) score, originally reported in 2005, consists of total lymphocyte counts (TL), total cholesterol level (T‐CHOL), and serum albumin (ALB) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The CONUT-PINK-E score targeted this challenge and provided vital theoretical guidance for clinical decision-making. Although few nutrition interventional studies for specific types of hematological tumors were being conducted (7), suggestions from clinical nutritionists and multidisciplinary consultations can favor to develop more rational treatment schedules, helping patients to endure long-term intensive chemotherapy. Furthermore, with the awareness of the relationship between malnutrition and malignancies, increasing number of nutrition interventional studies would be conducted and nutrition intervention schemes would be listed in the guidelines of cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since body resources are consuming, malnutrition is a common phenomenon in patients with advanced malignancies, accompanied with compromised immune competence, degressive physical activity and worsened clinical outcomes (5). Even though the prevalence and severity in ENKTL remain unclear, ENKTL patients are at high malnutrition risk due to the primary location and tumor burden (6,7). Nevertheless, nutritional status assessment has often been neglected in prognosis evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…There is a recent study showing that NRS‐2002 screening may not be essential before GLIM in patients with solid tumors, whereas whether the same conclusion can be drawn in lymphoma remains unclear 18 . Mancuso et al 19 reviewed the existing literature on interactions between malnutrition and lymphoma and noted that there is still no consensus on the best tool for nutritional assessment.…”
Section: Introductionmentioning
confidence: 99%